Behind bars ; Smokey/Art for all ; City insurgency [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1989)
Life behind prison bars. What goes on in the mind of a person behind bars; Hubert Araytn, an Austrian artist, finds that his art finds meaning in the lives of the resident of Smokey Mountain. Takes a look at insurgency problem in the City.
Behind bars (15 min.) -- Smokey/Art for all (13 in.) -- City insurgency (14 in.)
VHS.
Keywords: Aratym, Hubert -- Interviews; Alex Boncayao Brigade; Bilibid Prison; Prisoners -- Philippines; Insurgency -- Philippines